1999
DOI: 10.1128/jb.181.17.5273-5279.1999
|View full text |Cite
|
Sign up to set email alerts
|

HWP1 Functions in the Morphological Development of Candida albicans Downstream of EFG1 , TUP1 , and RBF1

Abstract: The morphological plasticity of Candida albicans is an important determinant of pathogenicity, and nonfilamentous mutants are avirulent. HWP1, a hypha-specific gene, was identified in a genetic screen for developmentally regulated genes and encodes a cell surface protein of unknown function. Heterozygous and homozygous deletions of HWP1 resulted in a medium-conditional defect in hyphal development. HWP1 expression was blocked in a Δefg1 mutant, reduced in an Δrbf1 mutant, and derepressed in a Δtup1 mutant. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(74 citation statements)
references
References 42 publications
5
66
0
3
Order By: Relevance
“…In contrast to CPH1, we found that EFG1 plays an important role by itself for transcription of several cell wall genes during morphogenesis. Many genes, including HWP1 and the newly identified HWP2, were downregulated in a Defg1 mutant strain under the hyphae-inducing conditions YPD + serum or a-MEM at 37∞C, confirming already published data that EFG1 is essential for the transcription of hyphae-specific genes (Sharkey et al, 1999;Braun and Johnson, 2000). This is also consistent with the fact that the induction of hyphae was impaired in the Defg1 mutant under these conditions ( Fig.…”
Section: The Role Of Efg1 In the Transcriptional Regulation Of Cell Wsupporting
confidence: 90%
“…In contrast to CPH1, we found that EFG1 plays an important role by itself for transcription of several cell wall genes during morphogenesis. Many genes, including HWP1 and the newly identified HWP2, were downregulated in a Defg1 mutant strain under the hyphae-inducing conditions YPD + serum or a-MEM at 37∞C, confirming already published data that EFG1 is essential for the transcription of hyphae-specific genes (Sharkey et al, 1999;Braun and Johnson, 2000). This is also consistent with the fact that the induction of hyphae was impaired in the Defg1 mutant under these conditions ( Fig.…”
Section: The Role Of Efg1 In the Transcriptional Regulation Of Cell Wsupporting
confidence: 90%
“…Nonetheless, the null mutant was severely affected in its capacity to develop hyphae on solid media. As the heterozygous camp65/CAMP65 mutant showed only partial inability to form hyphae, a gene-dosage effect is likely, as verified with other genes involved in filamentation pathways like the HWP1 gene (Sharkey et al, 1999;Tsuchimori et al, 2000) or some pH-regulated genes coding for cell wall proteins (Saporito-Irwin et al, 1995).…”
Section: Discussionmentioning
confidence: 79%
“…Solid medium 199 (M199 cat. n°31100-019, Invitrogen Corporation, Carlsbad, CA) was buffered with 150 mM Tris (pH 7) as previously described (Sharkey et al, 1999). Solid spider, serum and modified Lee's medium were prepared as described previously (Liu et al, 1994).…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 99%
“…We therefore examined the effect of DS1 on the HWP1 gene. HWP1 is a downstream component of the cAMP-dependent PKA pathway and is positively regulated by EFG1 (Sharkey et al 1999). In the present study, the transcript level of HWP1 decreased when treated with DS1 at 50 and 100 lg ml À1 .…”
Section: Discussionmentioning
confidence: 99%